2009
DOI: 10.1136/emj.2008.063958
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the oesophagus after penetrating cervical trauma using water-soluble contrast alone: simple, cost-effective and accurate

Abstract: A contrast study of the oesophagus with water-soluble iso-oncotic contrast media as the sole diagnostic imaging modality is safe (avoiding the risk of aspiration pneumonia), reliable (identifying all injuries) and cost-efficient (avoiding the need for additional expensive investigations) in cases of penetrating cervical trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Patients with clinical signs of ADTI or deep surgical emphysema need further investigation with a water‐soluble contrast swallow. This is generally sufficient to rule out any significant digestive tract injury, and reserves endoscopy for the comatose or uncooperative patient with suspected ADTI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with clinical signs of ADTI or deep surgical emphysema need further investigation with a water‐soluble contrast swallow. This is generally sufficient to rule out any significant digestive tract injury, and reserves endoscopy for the comatose or uncooperative patient with suspected ADTI.…”
Section: Discussionmentioning
confidence: 99%
“…It can show multiple signs such as widening of the superior mediastinum >8 cm and/or 25% of the width of the thorax (most common), loss of aortic knob, the obvious double contour of the aorta/abnormalities of the transverse aortic arch (sensitive finding), obliteration of the aortopulmonary window on lateral chest radiography (sensitive finding), massive hemothorax, and right deviation of the nasogastric, endotracheal, or esophageal tubes [8]. Normal vital signs with abnormal findings suggestive of a vascular injury should undergo CT aortography, the gold standard test, to confirm the diagnosis and facilitate operative planning since aortic injury grading is classified based on CT findings [25,34]. Signs on CT include abnormal aortic contour, sudden change in aortic caliber (pseudocoarctation), contained rupture, traumatic pseudoaneurysm, intimal flap, and intraluminal mural thrombus [25].…”
Section: Discussionmentioning
confidence: 99%
“…Signs on CT include abnormal aortic contour, sudden change in aortic caliber (pseudocoarctation), contained rupture, traumatic pseudoaneurysm, intimal flap, and intraluminal mural thrombus [25]. Alternatively, magnetic resonance imaging (MRI) of the thorax, conventional angiography, intravascular ultrasound (IVUS), or transesophageal echocardiogram (TOE) can be used as needed [25,34].…”
Section: Discussionmentioning
confidence: 99%
“…Our retrospective study, however, is in agreement with more recent studies concluding that water-soluble contrast esophogram alone is highly sensitive in evaluating esophageal injury or leaks. For example, Nel et al [9] showed a sensitivity of 100 %, specificity of 99.8 %, and negative predictive value of 99.6 % for esophageal injury/leak using only water-soluble contrast in penetrating cervical injuries. This is in line with our findings that water-soluble esophograms have sensitivity and negative predictive value of 100 %.…”
Section: Discussionmentioning
confidence: 99%